2000
DOI: 10.1046/j.1365-2648.2000.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of prone positioning for patients with acute respiratory distress syndrome

Abstract: This article presents an overview of a literature review on how prone positioning can alleviate pathophysiological changes in ARDS and improve ventilation and perfusion. Improvement of gas exchange, efficiency of oxygenation and lung function are emphasized. Literature on the pathophysiology of ARDS, and the physiological effects of prone positioning on haemodynamics and lung function is examined. There are both advantages and disadvantages in turning a patient from the supine to the prone position. There are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Studies conducted with individuals with pulmonary disease have shown, as in this study, oxygenation is better in a prone position (Breiburg et al . , Meade , Lin et al . , Das et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted with individuals with pulmonary disease have shown, as in this study, oxygenation is better in a prone position (Breiburg et al . , Meade , Lin et al . , Das et al .…”
Section: Discussionmentioning
confidence: 99%
“…The following complications were described while in the prone positions [ 28 , 30 , 42 , 43 , 65 , 105 , 124 , 144 , 218 , 272 , 301 ] facial oedema (20–30 %), pressure ulcers around the face/cornea, pelvis, knee (approximately 20 %) [ 234 ] ‘intolerance’ while in the prone position (= coughing, compaction, respiratory problems approximately 20 %), cardiac dysrhythmias (approximately 5 %), necrosis of the mamilla, pressure ulcers of the tibial crest (individual reports), dislocations of the tracheal tube or venous/arterial lines (approximately 1–2 %) [ 105 ], nerve damage (two case studies regarding brachial plexus lesion [ 119 ]) (evidence level 2b). In this regard, it is necessary to consider that complications also occur in the supine position and a comparison of the incidences of position-related complications for the prone position has not previously been sufficiently studied.…”
Section: Prone Position In Patients With Acute Pulmonary Disordersmentioning
confidence: 99%
“…Each positioning process—depending on the body weight of the patient as well as the invasiveness of the therapy (drainages, catheters, extensions)—is conducted by three to five nurses and one physician [ 13 , 17 , 18 , 42 , 138 , 190 , 195 , 207 , 254 , 260 , 276 , 303 , 304 ].…”
Section: Prone Position In Patients With Acute Pulmonary Disordersmentioning
confidence: 99%
“…There was no change in CI or wedge pressure, leading to the conclusion that this reduction may be related to a lower pulmonary vascular resistance. Increases and decreases in CI are seen in a few studies [49,61,70,71]. These variations may reflect use of different techniques in measuring CI versus an actual change in physiology [72].…”
Section: Prepositioning Assessmentmentioning
confidence: 99%